Improvement Pathway of Energy Transition: From the Perspective of Directed Technical Change - Hou, Guisheng; Song, Hongyu (Frontiers in Energy Research, 2022)
Energy transition can effectively promote the green transformation of economic development. With capital, traditional fossil energy, clean energy generation, thermal power generation, and the GDP of the provinces, we built a stochastic production frontier model based on a translog production function, which measures the bias of directed technical changes and substitution elasticities of 30 provinces in mainland China from 2000 to 2017. The results show that the directed technical change in China is more biased to thermal power generation and deviated from clean energy generation. In addition, except for traditional fossil generation and thermal power generation with a complementary relationship, there is a substitution relationship between other energy factors. At the regional level, the production patterns of 9 provinces (Beijing, Fujian, Hainan, Tianjin, Chongqing, Gansu, Neimenggu, Ningxia, and Xinjiang) are conducive to the external electric transition, and nine provinces (Beijing, Fujian, Guangxi, Hainan, Hubei, Jilin, Jiangsu, Qinghai, and Zhejiang) are beneficial to the internal electric transition. We find that there is a large room for improvement in external and internal electric transitions in most provinces. We propose that the Chinese government should promote the reform of the market-oriented energy pricing mechanism according to different production modes in different regions. Furthermore, the results from the analysis of China show that it is also possible for other countries to treat their energy transition differently due to their characteristic production patterns.